The Comparative Study on Anti-inflammatory Antioxidant and Antibacterial Effects with Regard to the Extraction Solvents of Ligustici Rhizoma - Hwang BoMin; Seo HyungSik (Korean Pharmacopuncture Institute, 2011)
Objective: This study was performed to compare anti-inflammation, anti-oxidation and anti-bacterial effects of Ligustici Rhizoma (LR) extracted with two kinds of solvents, ethanol and distilled water. Methods: It is prepared two kinds of LR extracts 20, 50, 100 ℃/㎎ by first. MTT assay way to measure cytotoxicity is formed in Raw 264.7 cell. The anti-inflammation effect is measured by ability to inhibit production of NO in Raw 264.7 cell. The anti-oxidation effect was measured by DPPH Radical scavenging ability in HaCaT cell. The anti-bacterial effect was measured by inhibition zone diameter on Propionibacterium acnes. Results: 1. LR (20 ㎕/㎎) extracted with ethanol was showed 80% cytotoxicity, LR (50 ㎕/㎎) extracted with ethanol and LR (20, 50 ㎕/㎎) extracted with water were showed 70% cytotoxicity, LR (100 ㎕/㎎) extracted with ethanol and LR (100 ㎕/㎎) extracted with water were showed 60% cytotoxicity in Raw 264.7 cell. 2. LR (100 ㎕/㎎) extracted with ethanol was showed more significantly inhibitory effect on NO production than the water extraction. 3. Two kinds of LR extraction groups did not show significantly scavenging effect of DPPH radicals. 4. Two kinds of LR extractions did not have a inhibitory effect on Propionibactrium acnes. Conclusion: Two kinds of LR extracts have not cytotoxicity, statistically significant ability to scavenge DPPH radicals and effect to inhibit Propionibactrium acnes. LR extracted with ethanol only have a little effect to inhibit NO production. This study proposes that LR extracted with ethanol is more effective in anti-inflammation.